6 - Conflict between National Interest and Human Rights: Britain’s Policy towards African Immigrants, 1960 – 2013 - Adeyeri, James Olusegun; Ogunniyi, Olayemi Jacob (Africa Development, 2021)
Since time immemorial, national interest has been the plank of inter-group and inter-State relations. In the modern contemporary international system, national interest has become the cornerstone of foreign policy formulation and actions of sovereign states. However, in pursuing and advancing national goals and objectives, each state is expected and required to conform to certain norms and standards of behaviour. One such is the respect for and observance of fundamental human rights, including freedom of movement, association, and other socio-economic self expressions. Experience has shown that the pursuit of national interest and preservation of fundamental human rights concurrently can be a daunting task for the state due to political, security, economic and social considerations. This article is a historical analysis of the conflicting postures of Britain’s African policy which in one breath, advocates and affirms commitment to human rights including those of free movement and association, but in another, undermines these same rights through certain immigration policies and practices. Pointedly, the article seeks to interrogate the basis, manifestations and implications of British immigration policy towards African immigrants between 1960 and 2013.